ANALYSIS OF TAX SOCIALIZATION AND EFFECTIVENESS OF THE APPLICATION OF E-FILLING TO THE COMPLIANCE OF PERSONAL TAXPAYERS REGISTERED IN BATAM - Sangkot Doris Sipayung; Vargo Christian L. Tobing (Jurnal Ekonomi, 2023)
Tax is one of the biggest revenues of a country. The increase in tax revenue every year is always changing. This study aims to determine the effect of tax socialization and the effectiveness of e-filling implementation on compliance of personal taxpayers registered at KPP Pratama Batam Selatan either partially or simultaneously. The method in this research is descriptive with a quantitative approach. The population taken in this study were individual taxpayers registered at the South Batam Primary Tax Service Office, Batam city, Riau Islands Province which amounted to 353,613 taxpayers in 2021. The sample taken in this study was 100 taxpayers where the existing taxpayers were calculated using the Slovin formula. The level of taxpayer compliance in Batam city has not been maximized due to taxpayers who have not reported their taxes. The government creates easy steps for taxpayers to report taxes by using e-filling. With the use of e-filling, it is expected to increase taxpayer compliance in the city of Batam. The results of the research with the tests carried out explain that: 1) tax socialization has no significant effect on taxpayer compliance, 2) the effectiveness of the application of e-filling has a significant effect on taxpayer compliance, 3) tax socialization and the effectiveness of the application of e-filling simultaneously affect taxpayer compliance, where the coefficient of determination (R2) is 29.1% and the remaining 71.9% is influenced by other variables not included in this study.